A Review on the Supply and Demand of Coffee in Cambodia - Tal Sokly; Serey Mardy (International Journal of Sustainable Applied Sciences, 2023)
The demand for coffee in Cambodia is also growing, driven by a number of factors, including the increasing popularity of coffee shops and cafes, the rising incomes of Cambodians, and the growing influence of Western culture. This growing demand is putting a strain on domestic supply, and Cambodia now imports more coffee than it produces. In 2020, Cambodia imported around 770 tons of coffee beans, mainly from neighboring countries such as Vietnam and Laos. A qualitative method combined with a descriptive analytic approach is the methodology addressed. The data is review from relevant sources on the supply and demand of coffee in Cambodia include academic papers, government reports, industry reports, and news articles. found that the coffee sector in Cambodia has the potential to generate significant economic and social benefits for the country. The study found that the coffee sector could create up to 100,000 new jobs and generate $500 million in revenue by 2025. The study also found that the coffee sector could help to reduce poverty and improve the livelihoods of rural communities. Coffee is a relatively high-value crop, and coffee farmers can earn significantly more than farmers who grow other crops. An estimated 9,650 tons of coffee were consumed in Cambodia in 2022. This represents a significant increase from 2014, when Cambodians consumed only 5,970 tons of coffee. In 2020, Cambodia produced around 3,900 tons of coffee, and the government has a goal of increasing production to 10,000 tons by 2025.